Enhancement of Piezoelectricity in Dimensionally Engineered Metal‐Halide Perovskites Induced by Deep Level Defects. Issue 19 (8th April 2022) - Heo, Sung; Lee, Do Yoon; Lee, Dongwook; Lee, Yonghui; Kim, Kihong; Yun, Hyun‐Sung; Paik, Min Jae; Shin, Tae Joo; Oh, Hyeon Seung; Shin, Taeho; Kim, Jaekyung; Kim, Seong Heon; et al.
Abstract: Metal halide perovskite solar cells (PSCs) have been considered to be one of the most promising next‐generation energy harvesters over the past decades due to remarkably rapid improvement of power conversion efficiency in photovoltaics. However, energy harvesters based on the solar energy source have an intrinsic environment limitation for indoor applications. A feasible solution to the limitation is to add non‐solar energy harvesting functions to the solar energy harvesters. Here, the piezoelectric properties of two types of metal halide PSCs are investigated, the 3D only and the 3D/2D structure, showing PCEs of 21.3% and 23.2%, respectively. Piezo‐response force microscopy and synchrotron‐based X‐ray diffraction demonstrate that both types of PSC sample have piezoelectricity. Remarkably, the 3D/2D structure has considerably higher piezoelectric amplitude than the 3D‐only. The deep level transient spectroscopy results reveal that the enhancement in the piezoelectricity of the 3D/2D structure originates from PbBr defects. This study unravels the role of defects in the piezoelectricity of metal halide PSCs and provides a direction to develop the multi‐function energy harvesters based on the PSCs. Abstract : The piezoelectric properties of two types of metal halide perovskite solar cells (PSCs), the 3D and the 3D/2D structure are investigated. It is found that the 3D/2D structure has a considerably more intense piezoelectric features than the 3D‐only one. The deep level transient spectroscopy measurement unveils that the PbBr defects play a crucial role in enhancing piezoelectric properties for the PSCs of the 3D/2D heterostructure, which unravels the correlation between the deep level defects and piezoelectric properties in PSCs.